Nitrogen and sulfur dual-doped graphene sheets as anode materials with superior cycling stability for lithium-ion batteries. (1st December 2015) - Zhou, Yuqi; Zeng, Yan; Xu, Dandan; Li, Peihang; Wang, Heng-guo; Li, Xiang; Li, Yanhui; Wang, Yinghui
Abstract: Novel nitrogen and sulfur dual-doped graphene sheets are synthesized via carbonization of poly(2, 5-dimercapto-1, 3, 4-thiadiazole) (PDMcT) functionalized graphene oxides. Here, PDMcT, polymerized by the commercially available 2, 5-dimercapto-1, 3, 4-thiadiazole (DMcT) monomer is chosen as the nitrogen and sulfur precursor, which plays a key role in the formation of nitrogen and sulfur dual-doped graphene. When evaluated as anode materials for lithium ion batteries, the nitrogen and sulfur dual-doped graphene sheets show high initial specific capacity of 1428.8 mAh g −1, excellent cycling stability over 5000 cycles, and good rate capability (107 mAh g −1 even at a current density of 10 A g −1 ), which can be attributed to the unique structure and dual-heteroatom doping.